2008
DOI: 10.1080/01431160701408360
|View full text |Cite
|
Sign up to set email alerts
|

ASTER‐based study of the night‐time urban heat island effect in Metro Manila

Abstract: The Advanced Spaceborne Thermal Emission and Reflection Radiometer (ASTER) was used to derive land surface temperatures to quantify the nighttime urban heat island (UHI) effect in Metro Manila. Temperature differences between Metro Manila and its adjacent rural towns were compared to determine heat island intensity and analyse spatial variation of surface temperature. Transects were drawn across from the rural to the urban region to characterize the UHI profile and the Normalized Difference Vegetation Index (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(49 citation statements)
references
References 40 publications
1
46
0
2
Order By: Relevance
“…Many studies following this approach found a negative correlation between vegetation indices such as NDVI (normalized difference vegetation index) and temperature (Hung et al, 2006;Tiangco et al, 2008). This is consistent with the hypothesis that green cover may be effective in reducing temperature.…”
Section: Introductionsupporting
confidence: 61%
“…Many studies following this approach found a negative correlation between vegetation indices such as NDVI (normalized difference vegetation index) and temperature (Hung et al, 2006;Tiangco et al, 2008). This is consistent with the hypothesis that green cover may be effective in reducing temperature.…”
Section: Introductionsupporting
confidence: 61%
“…The decreasing vegetation and increasing impervious surfaces can increase heat stored during daytime. Therefore, more heat will be released from impervious surfaces during nighttime, leading to the increasing nighttime SUHII [25,55]. One unique phenomenon was that the SUHII was significantly negatively correlated with ∆EVI at 4 of 10 cities in winter nights.…”
Section: The Relationships Between Suhii and ∆Evimentioning
confidence: 87%
“…Airborne acquired high-resolution images were also used to assess the thermal determiners of urban surfaces such as sky view factor and surface materials [19]. The ASTER is another sensor of the TIR image that collects both daytime and night-time data and has been used for determining the UHI effect in many cities [56][57][58].…”
Section: Satellite Measurements Of Urban Heat Islandmentioning
confidence: 99%